(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Globally, infectious illnesses continue to be a major source of morbidity and mortality, especially in low- and middle-income nations. Each area, pathogen, and route of transmission has a different epidemiology of infectious illnesses. This study examines the prevalence of infectious illnesses worldwide, emphasizing the respiratory, vector-borne, waterborne, and contact modes of transmission. It also assesses how well preventative measures work to stop the spread of infections. A comparative examination of incidence, death, and preventative efficacy is provided based on data taken from international health organizations. The findings imply that certain treatments, such immunization, vector control, and better sanitation, can considerably lower the incidence of illness. However, in many areas, effective prevention and control are hampered by worldwide inequities in healthcare access.